Public Expenditure and Economic Growth in Nigeria: A Multivariate Approach to Wagner's Hypothesis - Gregory Onyekachi Ezedike (IIARD INTERNATIONAL JOURNAL OF BANKING AND FINANCE RESEARCH, 2026)
This study examined the effect of Public Expenditure on Economic Growth in Nigeria for the period 1985 to 2023 using data from the CBN Statistical Bulletin 2022. The model used Real Gross Domestic Product (RGDP) for economic growth while Public Expenditure is measured in Expenditure on Administration (ADM), Expenditure on Economic Services (ECONS), Expenditure on Social and Community Services (SOCS), and Expenditure on Transfers (TRANS). It factored Inflation rate (INF) as a control variable. The Autoregressive Distributive Lag (ARDL) revealed long run relationship in the model. It also revealed that ADM has significant positive effect on RGDP in the short run and in the long run; ECONS has significant negative effect on RGDP both in the short run and in the long run; SOCS has significant positive effect on RGDP in the short run and in the long run; while TRANS has insignificant negative effect on RGDP in the short run and in the long run. The findings led to the conclusion that government expenditure significantly affects economic growth in Nigeria, recommending the need to scrutinize the government expenditure on economic services and implement proper mechanisms such as boosts in EFCC and ICPC surveillance that will ensure transparent management.